EVOLUTION OF SCIENTIFIC THOUGHT ON THE ROLE OF SOCIAL CAPITAL IN ECONOMIC DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article reveals the evolution of scientific views on the role of social capital in economic development. The scientific views of researchers from A. Smith to the present on the nature and channels of influence of social capital on the economic system and the welfare of economic agents in particular are systematized. The role of research of Nobel laureates K. Arrow, E. Ostrom, A. Sen in the development of the theory of social capital and the study of its economic effects is revealed. The place of M. Tugan-Baranovsky's scientific achievements in the formation of the concept of social capital is characterized. The author 's periodization of the development of the theory of social capital and perspective directions of its research are offered.The periodization of the development of the theory of social capital is carried out with the separation of the following stages: 1) XVIII century - until the 1970s - the formation of basic scientific ideas about group cooperation as a factor in ensuring the efficiency of economic activity, 2) 1970s-1980s - the beginning of the study of economic consequences of social capital development at the micro-level; 3) 1990s - the beginning of the XXI century - expanding the scope of research of the economic potential of social capital from micro- to meso- and macro-levels, 4) the beginning of the XXI century – till now - shifting the focus of scientific discourse from theoretical to practice-oriented research on the economic return of social capital.It was found that scientific views on the place of social capital in the development of socio-economic processes have evolved significantly: from studying its importance in the formation of human capital to the role in education, health, economic growth, poverty reduction, income inequality and more. However, despite the diversity of such studies, the issues of the interaction of social capital development, on the one hand, and innovation, entrepreneurship, financial markets, state and local self-government, on the other, remain insufficiently studied; and the role of social capital in ensuring sustainable development.
Keywords: social capital, economic development, the genesis of the concept of social capital